EFFECT OF CHLORAL HYDRATE ON METABOLIC RATE OF LABEO ROHITA (HAM) AND POECILIA RETICULATA (PETERS) - SHARMA, L. L.; SHARMA, S. K. (Journal of Indian Fisheries Association, 2015)
Comparative impact of chloral hydrate anaesthesia on the metabolicrate of Indian major carp Labeo rohita and larvivorous fish Poeciliareticulata was assessed. Observation on the oxygen consumption rate(OCR) revealed that in common guppies OCR was substantially low (1.105and 1.097 mg/g!hr) at 0.1 and 0.25 gil concentrations of chloral hydrate asagainst OCR of 1.487 mg/g/hr in the control. Fry of L.rohita in groupÂ·showed lower metabolic rates in the control as well as treated conditionsas compared to the individuals of this fish. This may be due to sympatheticpsychophysiological reflex of grouped fish. Higher dose of chlo1Â·al hydrate(0.25g!l) also caused higher OCR probably due to distress. Application ofchloral hydrate also favoured lesser release of metabolic wastes (ammoniaand carbon dioxide). There was significant positive correlation betweentime and oxygen consumption, whereas, for time and OCR this relationshipwas negative. Regression of chloral hydrate doses for OCR and time hasalso been calculated.